El cheque y su importancia como mecanismo de pago en el Ecuador. - Echeverria Barros, Yadira Estefania (My University, 2018)
The word check that denominates the credit title whose examination is the object of this work. The importance and transcendence of the economic functions of the check, derive from its consideration of means or instrument of payment. The use of the check in the payments implies important advantages in the particular and general aspects.Fundamentally it is an instrument or means of payment that economically substitutes the payment in money. The purpose of the check is to be used as an instrument of money circulation, as a means of payment, instead of the legal currency. The object of the present investigation is to carry out an analysis on the proper turning of checks to avoid inconveniences in their collection. This investigation was based on the descriptive and documentary method. Being the descriptive method necessary to present the current situation of this document, its use and importance; while the documentary research allows to make its theoretical sustenance based on books, indexed journals, reports, among others.
La palabra cheque que denomina al título de crédito cuyo examen constituye el objeto de este trabajo. La importancia y trascendencia de las funciones económicas del cheque, derivan de su consideración de medio o instrumento de pago. El empleo del cheque en los pagos implica importantes ventajas en los aspectos particular y general. Fundamentalmente es un instrumento o medio de pago que sustituye económicamente al pago en dinero. El destino del cheque consiste en ser usado como instrumento de circulación de dinero, como medio de pago, en lugar de la moneda legal. El objeto de la presente investigación es el de realizar un análisis sobre el adecuado giro de cheques para evitar inconvenientes en su cobro. Esta investigación se basó en el método descriptivo y documental. Siendo el método descriptivo necesario para presentar la situación actual de este documento, su uso e importancia; mientras que la investigación documental permite realizar su sustento teórico en base a libros, revistas indexadas, informes, entre otros.
Keywords: SISTEMA BANCARIO; INTERÉS; TITULO DE VALOR; CHEQUE; BANCO